Income inequality in Germany temporarily sinks during crises - Geraldine Dany-Knedlik; Alexander Kriwoluzky (DIW Weekly Report, 2021)
This study is the first to investigate the interdependence of income inequality and business cycles in Germany over the past 40 years. These fluctuations in income inequality are important because they are decisive for designing effective and targeted structural redistributive and stabilization measures. The results of this study show that income inequality in Germany fluctuates with the business cycle procyclically. Thus, gross and net income inequality decrease during economic crises and increase during recovery periods. This is mainly due to the fact that the percentage loss or gain of income of the ten percent with the highest incomes is higher than those of individuals with lower incomes. Stabilization policies that cushion income losses during crises, such as the short-time work allowance, reinforce the procyclicality slightly and counteract inequality, especially in crises. This procyclicality is desirable from a political perspective and has a welfare- enhancing effect by, for example, providing social security for low-income earners against negative shocks. However, to what extent the corresponding increase in income inequality during booms must be tolerated remains unclear.
Keywords: E01; E32; D31; 330; income inequality; business cycle; German economy